O człowieku, cielesności i śmierci w perspektywie filozofii Emmanuela Lévinasa - Brzózy, Nikodem Zbigniew (Poznańskie Studia Teologiczne, 2008)
The article is an attempt to link the philosophy of Levinas with the bioethical issues of the beginning of human life. The author refers to those statements of Levinas in which he describes who a person is, what is human body, being male/female, fatherhood. The ethical-anthropological character of Levinas’ thought makes it a profound source for contemporary discussions on moral themes, bioethical problems included. However, certain difficulties arise on account of the philosopher’s highly individual language. The aim of the article is to confront the language o f Levinas with the traditional language of Aristotelian-Thomistic philosophy and colloquial language. The text is a proposition how to build bioethics not only on Aristotelian-Thomistic philosophy or utilitarian or pragmatic philosophy but also on the philosophy of Levinas, as it sheds additional light on the problem of man, existence, life and interpersonal relations.